1993
DOI: 10.1093/bja/70.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and Catecholamine Responses to Induction of Anaesthesia and Tracheal Intubation: Comparison Between Propofol and Thiopentone

Abstract: We have studied the haemodynamic changes, QT intervals and catecholamine responses to induction of anaesthesia and tracheal intubation in 24 ASA I patients allocated randomly to receive either propofol 2.5 mg kg-1 or thiopentone 5 mg kg-1 over 60 s. After disappearance of the eyelash reflex, the lungs were ventilated with 100% oxygen for 3 min. The trachea was intubated after administration of vecuronium. With thiopentone, heart rate (HR) was greater than with propofol before intubation (P < 0.05). During indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 0 publications
5
79
0
4
Order By: Relevance
“…SBP, DBP decreased significantly after propofol prior to intubation whereas there was significant increase in arterial pressure after intubation after Thiopentone in all three groups. The results were confirmed by S.Coley et al 12 , C. C. Tzen 13 14 .…”
Section: Discussionsupporting
confidence: 60%
“…SBP, DBP decreased significantly after propofol prior to intubation whereas there was significant increase in arterial pressure after intubation after Thiopentone in all three groups. The results were confirmed by S.Coley et al 12 , C. C. Tzen 13 14 .…”
Section: Discussionsupporting
confidence: 60%
“…Lindgren et al [15], found that tracheal intubation increases heart rate, blood pressure, catecholamine levels and the QTc interval, and that the continuous infusion of catecholamine leads to QTc interval prolongation and amplifies the U wave [23]. Increased plasma catecholamine is related to QTc prolongation and cardiac arrhythmias.…”
Section: ó 2008 the Authorsmentioning
confidence: 99%
“…Generally, it is known that tracheal intubation during induction stimulates sympathetic activity, which, as a result, prolongs the QTc interval [15,16]. In contrast, other studies have shown the opposite, with tracheal intubation decreasing the QTc interval [17].…”
mentioning
confidence: 99%
“…7, 8. 201, while propofol does not [20]. In the present study all patients were prernedicated with midazolam and this may have influenced the results, though we have recently found in a similar study (unpublished observations) that midazolam does not produce any significant changes in QTc.…”
Section: Discussionmentioning
confidence: 49%
“…No patient in the halothane group showed any ST depression although seven patients developed a nodal rhythm and in two patients, ventricular extrasystoles were observed. It is unfortunate that the ST segment depression could not be accurately measured because the ECG monitor had no hcilities for voltage calibration (20) 418 (17) 411 (22) 116 (11) 93 (11) 85 (10) 71 (8) 53 (12) 48 (10) 92 (18) 470 (25) 86 (13) 45 (9) 66 (12) 419 (21) 81 (10) (13) 87 (22) 97 (28) 91 (21) 40 (8) 41 (8) 59 (20) 50 (17) 65 (14) 68 (14) 86 (22) 77 (18) 413 (21) 415 (26) 436 (29) Table 2). The differences in HR between the two groups were significant at all times (p<O.OOI), (Fig.…”
Section: Ecgmentioning
confidence: 99%